Penerapan Blended Project Based Learning dengan Media Canva Terintegrasi Website Bioenial Sebagai Upaya Meningkatkan Keterampilan Proses Sains dan Life Skills - Susanti, Retno; Sugiharto, Bowo; Prayitno, Baskoro Adi (Cetta: Jurnal Ilmu Pendidikan, 2025)
The purpose of this study is to explore the effectiveness of the implementation of Blended Project-Based Learning with Canva media integrated with the Bioennial Website as an effort to improve low science process skills and life skills. The literature review is the selection of research methods with literature sources from various journals indexed by Google Scholar and Scopus. The study population is research journals relevant to topics for various levels of study, from Early Childhood Education to Higher Education. The search criteria are journals ranging from 2020-2025, containing keywords similar to the research topic, and full papers. The search results of journals that meet the specified inclusion criteria found a total of 940 journals. Of these, 10 journals were obtained that fit the objectives of this study. The findings showed an increase in the effectiveness of students' independent learning abilities and ease of teachers in flexible time. It can be concluded that the implementation of Blended Learning that integrates innovative and creative elements such as the Project-Based Learning model with Canva media integrated with the Bioennial Website that utilizes technology effectively, shows great potential to improve science process skills and life skills. However, achieving maximum results requires challenges that must be faced and overcome, one of which is the role of the curriculum in integrating digital technology and digital literacy to ensure that students and teachers have the space and support to develop adaptively.